Laser light scattering from silicon particles generated in an argon diluted silane plasma. (27th January 2016) - Qin, Y; Bilik, N; Kortshagen, U R; Aydil, E S
Abstract: We conducted laser light scattering (LLS) measurements in a 13.56 MHz capacitively coupled dusty plasma maintained in silane and argon to study the spatial distribution of silicon nanoparticles and nanoparticle agglomerates. Specifically, we focused on the temporal evolution of their spatial distribution in the plasma as a function of pressure and power. We observed three distinct types of temporal evolution behavior of the nanoparticle dust cloud in the plasma and classified these into three regimes based on pressure and power. Each regime features a distinct pattern in laser light scattering measurements. At low pressures (̃80–100 mTorr) and high powers (̃40–60 W) we observed periodically repeating expansions and contractions of a continuous dust cloud for the first time. Dust voids, which have been reported before, were also observed at high pressures (̃100–150 mTorr) and low powers (̃20–40 W) in the center of the plasma. A mechanism is proposed to explain the observed dynamics of the nanoparticles. The balance between the ion drag force and electrostatic forces and their dependence on particle size are hypothesized to be the dominant factors that determine the nanoparticle cloud dynamics.